Why do Polish Women Want to Stay Childless? Analysis of Voluntary Childlessness Motives - Wilak, Justyna (Dlaczego polskie kobiety chcą pozostać bezdzietne? Analiza motywów dobrowolnej bezdzietności, 2023)
The phenomenon of voluntary childlessness is increasingly apparent in the modern world contributing to the problem of an ageing society. There are numerous motives of voluntary childlessness indicated in the literature that are especially related to the decisions of women. The aim of this study was the identification of the motives for voluntary childlessness among Polish women using internet debate analysis. The analysis indicated nine motives: desire for freedom, the need for peace and solitude, reluctance to make sacrifices/to take additional responsibilities, dislike of children, fear of pregnancy and childbirth, fear of potential disease of a child, environmental motives, the lack of maternal instinct and bad childhood experiences that can be classified in three categories.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2023; vol. 67, nr 3, s. 130-141
Keywords: voluntary childlessness; motives of childlessness; qualitative study; dobrowolna bezdzietność; motywy bezdzietności; badania jakościowe